Analisis Pengaruh Store Atmosphere Terhadap Keputusan Pembelian pada Jodo Plaza Purworejo - Achmad Thafthazani; Wiyonoroto Wiyonoroto; Rusmiyatun Rusmiyatun (STIE Rajawali Purworejo, 2024)
This study aims to determine whether partially general interior, store layout, and interior display have a positive and significant effect on purchase decisions, and to simultaneously determine whether store exterior, general interior, store layout, and interior display have a positive and significant effect on purchase decisions. The research was conducted on consumers at Jodo Plaza Purworejo. The study was analyzed using multiple linear regression analysis with t-tests and F-tests involving the variables store exterior (X1), general interior (X2), store layout (X3), interior display (X4), and purchase decisions (Y). The calculation results yielded the regression equation Y = 2.466 + 0.784 X1 + 0.254 X2 + 0.354 X3 - 0.112 X4 + e. This means that if the values of store exterior, general interior, store layout, and interior display variables on the research object are equal to zero, then the level or magnitude of the purchase decision variable is 2.466. The testing of the first hypothesis (H1) resulted in a significance value (sig) of 0.00 (P<0.05) and a positive value of 8.660, meaning that partially, store exterior (X1) has a significant effect on purchase decisions (Y) and is accepted. The second hypothesis (H2) yielded a sig value of 0.002 (p < 0.05) and a positive value of 3.192, meaning that partially, general interior (X2) has a significant effect on purchase decisions (Y) and is accepted. The third hypothesis (H3) produced a sig value of 0.000 (p < 0.05) and a positive value of 4.763, meaning that partially, store layout (X3) has a significant effect on purchase decisions (Y) and is accepted. The fourth hypothesis (H4) resulted in a value of 0.153, and the t-test showed -1.441. With a sig value of 0.153 (p > 0.05) and a negative value of -1.441, it means that partially, interior display (X4) has a significant effect on purchase decisions (Y) and is rejected. The ANOVA test yielded an F-value of 102.521, with a positive significant value of 0.000 (p < 0.05), indicating that the fifth hypothesis (H5) that store exterior, general interior, store layout, and interior display simultaneously have a significant effect on purchase decisions (Y) and is accepted.